Anchorage management of a hiperdivergent Class II division 1 malocclusion with severe crowding using orthodontic miniscrew - Adisty Setyari Putri; Haru Setyo Anggani (Journal of Dentomaxillofacial Science, 2021)
Objective: Hyperdivergent Class II division 1 malocclusion with severe crowding generally requires premolars extraction to create space for crowding correction, anterior retraction, and facial profile improvement. The purpose of this case report is to demonstrate the anchorage management of a hyperdivergent Class II division 1 malocclusion with severe crowding using orthodontic miniscrew as skeletal anchorage.Method: This case was treated by extraction of the upper and lower first premolars, using a conventional orthodontic appliance MBT system and orthodontic miniscrew as skeletal anchorage. Result: Correction of severe crowding, protrusive incisors, and improvement of the facial profile were obtained in 26 months of treatment.Conclusion: Anchorage management with orthodontic miniscrew was effective in correcting severe crowding, protrusive incisors, and convex facial profile of a hyperdivergent Class II division 1 malocclusion